(untitled) (INNOVATIVE ECONOMY, 2020)
Kysil S.S. STATE REGULATION AND FINANCIAL SUPPORT OF AGRICULTURAL ENTERPRISES INNOVATIVE DEVELOPMENT Purpose. The objectives of the study are to identify the main components of the state policy of financial support for the innovation activities of agricultural enterprises and to develop the main directions of state regulation of financial support for their innovative development. Methodology of research. The theoretical and methodological basis of the study is a systematic approach to the knowledge of the fundamental principles of economics regarding the financial support for the innovative development of agricultural enterprises. To achieve the goal and solve the tasks, a system of in-scientific and special methods was used, namely: integral assessment – to determine the level of financial support for the innovative development of agricultural enterprises and the expert assessments – to identify current trends in state financial support for enterprises. Findings. The essence of financial support of the agrarian sector is presented. The position of Ukraine in the global innovation ranking and the level of global competitiveness is presented. The problems of innovative activity financing in Ukraine has been identified. The modern trends of state financial support of enterprises activity are revealed. Originality. The priority directions of the state regulation of financial provision of innovative development agricultural enterprises are offered. Practical value. The results of the study are the basis for the development of the main directions of state regulation of financial support for the innovative development of agricultural enterprises. Key words: state regulation; state financial support; financial provision; innovation activity; innovation development; agricultural enterprises; agrarian sector.